Exploiting a hybrid lithium ion power source with a high energy density over 30 Wh/kg. (March 2018) - Jin, Liming; Zheng, Junsheng; Wu, Qiang; Shellikeri, Annadanesh; Yturriaga, Steven; Gong, Ruiqi; Huang, Jun; Zheng, Jim P.
Abstract: Lithium ion capacitor (LIC) with high energy density, high power density, as well as long cycle life, is considered as one of the most promising energy storage and conversion system. However, in practical level, the energy density of LIC can hardly breakthrough 20 Wh kg −1 full cell, which largely limits its applications. Hence, in this study, a new type of hybrid lithium ion power source (hLIPS), which is fabricated using lithium iron phosphate (LFP)/activated carbon (AC) composite cathode and Li doped hard carbon (HC) anode, and characterized in Li-containing organic electrolyte, is proposed to further enhance the energy density of LIC. Based on this design, a prototype pouch cell with a capacity of 300 F at 1 C has been produced. Operating in a range of 2.2–3.8 V, this device with a breakthrough energy density of ca. 30 Wh kg −1 full cell, high power density of 2000 W kg −1 full cell, as well as long cycle life over 30000 cycles (90% retention), has enormous prospect to promote the energy density of LIC to enlarge the application field. Graphical abstract: Highlights: A hybrid lithium ion power source (hLIPS) is designed and proposed. The hLIPS is capable to deliver a breakthrough energy density over 30 Wh/kg much higher than lithium ion capacitor. The hLIPS has not sacrificed power density and cycle life in comparison with lithium ion capacitor. The hLIPS will enlarge the application field of energy storage devices.